Determination of Radiation Doses to Patients Undergoing Fluoroscopically Guided Orthopaedic Procedures at Muhimbili Orthopaedic Institute in Tanzania - Busumabu, Jacob; Makundi, Ismael N.; Ngaile, Justin E. (Tanzania Journal of Science, 2021)
The aim of the present study was to determine the magnitude of radiation doses delivered to patients undergoing Fluoroscopically Guided Orthopaedic Procedures (FGOP’s) in Tanzania. The air Kerma Area Product (KAP), fluoroscopy time, organ dose and effective dose to patients undergoing FGOP’s were obtained from Muhimbili Orthopaedic Institute. A total of 72 adult patients from selected three FGOPs namely Lumbar Spine (LS), Dynamic Hip Screw (DHS) and Thoracic Spine (TS) procedures were investigated using C-arm fluoroscopy machine. The knowledge of patient demographic data, radiographic data, KAP and Monte Carlo-based PCXMC software were used to obtain the magnitude of organ doses (OD) and effective doses (ED) of the patients.The median values of KAP for the LS, DHS and TS were 2.569, 2.410 and 0.770 Gy cm2, respectively. The mean values of ED for the LS, DHS, and TS procedures were 0.27, 0.47 and 2.70 mSv, respectively.The observed wide variations of KAP, organ dose, effective and exposure protocols within the hospital under study and relative high dose in this study compared to reported values from the literature call for standardization of procedural protocols and optimize fluoroscopically guided orthopaedic procedures.